Detecting tumour-positive resection margins after oral cancer surgery by spraying a fluorescent tracer activated by gamma-glutamyltranspeptidase. (March 2018) - Slooter, Maxime D.; Handgraaf, Henricus J.M.; Boonstra, Martin C.; van der Velden, Lily-Ann; Bhairosingh, Shadhvi S.; Que, Ivo; de Haan, Lorraine M.; Keereweer, Stijn; van Driel, Pieter B.A.A.; Chan, Alan; Kobayashi, Hisataka; Vahrmeijer, Alexander L.; et al.
Highlights: gGlu-HMRG spray becomes fluorescent upon activation by gamma-glutamyltranspeptidase. This mechanism occurs in vivo and ex vivo (fresh tissue and frozen sections) This technique can enable screening for tumour-positive resection margins. Abstract: Objectives: Tumour-positive resection margins are a major problem during oral cancer surgery. gGlu-HMRG is a tracer that becomes fluorescent upon activation by gamma-glutamyltranspeptidase (GGT). This study aims to investigate the combination of gGlu-HMRG and a clinical fluorescence imaging system for the detection of tumour-positive resection margins. Materials and methods: The preclinical Maestro and clinical Artemis imaging systems were compared in vitro and ex vivo with cultured human head and neck cancer cells (OSC19, GGT-positive; and FaDu, GGT negative) and tumour-bearing nude mice. Subsequently, frozen sections of normal and oral cancer tissues were ex vivo sprayed with gGlu-HMRG to determine the sensitivity and specificity. Finally, resection margins of patients with suspected oral cancer were ex vivo sprayed with gGlu-HMRG to detect tumour-positive resection margins. Results: Both systems could be used to detect gGlu-HMRG activation in vitro and ex vivo in GGT positive cancer cells. Sensitivity and specificity of gGlu-HMRG and the Artemis on frozen tissue samples was 80% and 87%, respectively. Seven patients undergoing surgery for suspected oral cancer were included. In three patients fluorescence was observed at the resection margin. Those margins were either tumour-positive or within 1 mm of tumour. The margins of the other patients were clear (≥8 mm). Conclusion: This study demonstrates the feasibility to detect tumour-positive resection margins with gGlu-HMRG and a clinical fluorescence imaging system. Applying this technique would enable intraoperative screening of the entire resection margin and allow direct re-resection in case of tumour-positivity.